2022
DOI: 10.3389/fpsyg.2022.853168
|View full text |Cite
|
Sign up to set email alerts
|

Let's Buy With Social Commerce Platforms Through Social Media Influencers: An Indian Consumer Perspective

Abstract: The COVID-19 pandemic has had a substantial impact on the retail industry around the globe, including in the vast market of India. The response to the pandemic required stores to close and develop new ways to approach shoppers more efficiently. The worldwide usage of social media enabled the growth of social commerce (s-commerce). Influencers on s-commerce platforms use live broadcasting on their channels to promote endorsed products. The features of s-commerce influencers enhance users' trust in the online co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…The findings showed that customers' intentions to make online purchases are significantly positively impacted by trust in SMIs. Thus, this study establishes that followers’ trust is paramount for any online shopping; very few research studies have considered the impact of SMIs on customers’ online buying behaviour (Alam et al. , 2022; Zhang et al.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 74%
See 4 more Smart Citations
“…The findings showed that customers' intentions to make online purchases are significantly positively impacted by trust in SMIs. Thus, this study establishes that followers’ trust is paramount for any online shopping; very few research studies have considered the impact of SMIs on customers’ online buying behaviour (Alam et al. , 2022; Zhang et al.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 74%
“…The findings showed that customers' intentions to make online purchases are significantly positively impacted by trust in SMIs. Thus, this study establishes that followers' trust is paramount for any online shopping; very few research studies have considered the impact of SMIs on customers' online buying behaviour (Alam et al, 2022;Zhang et al, 2020). Trust in the influencer also has a direct impact on the credibility of the influencer's message (Mart ınez-L opez et al, 2020), indicating that trust is the foundation that creates reliability for any post done by the influencers on a social media platform.…”
Section: Theoretical and Managerial Implications 61 Theoretical Impli...mentioning
confidence: 76%
See 3 more Smart Citations